Analisis Kinerja Keuangan Melalui Rasio Profitabilitas Pada UMKM Zenfood Frozen Malang - Shany Putri Nabilla; Hanifiyatussamha Adieb; Davina Pink Aulia Mirza; Mohamad Bastomi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine financial performance through profitability ratios at Zenfood Frozen MSMEs located on Jalan Ir. Rais IX Malang City. The approach used in this research is a Quantitative Descriptive approach. The data used is primary data collected through a process of direct observation, interviews, and documentation, regarding variable costs, revenues and profits that occur. Data analysis uses profit analysis to determine the amount and value of product sales using income analysis. This study describes the profitability ratios at UMKM Zenfood Frozen Malang as follows Gross Profit Margin in May was 36.4% and June was 39.1%, Net Profit Margin in May was 34.8% and June was 35.6%, ROA in May was 43.4% in June was 47.5% ROE in May was 65.1% and June was 62.4%. The results of the calculation of profitability ratios in Zenfood Frozen MSMEs according to Industry Profitability Ratio Standards, the results of the calculation of gross profit margin, net profit margin, ROA and ROE for the May-June period are above the industry standard average. Zenfood Frozen business owners are advised to continue to monitor and analyze business profitability regularly.